The potential role of suppressors of cytokine signaling (SOCS) in the attenuation of inflammatory reaction and alveolar bone loss associated with apical periodontitis - Menezes, Renato (2008)
Inflammatory cytokines contribute to periapical tissue destruction. Their activity is potentially regulated by SOCS (suppressors of cytokine signaling), which downregulate signal transduction as part of an inhibitory feedback loop. We investigated the expression of the cytokines TNF-α, IL-10 and RANKL, and SOCS-1, -2 and -3 by Real Time-PCR in 57 periapical granulomas and 38 healthy periapical tissues. Periapical granulomas exhibited significant higher SOCS-1, -2 and -3, TNF-α, IL-10 and RANKL mRNA levels when compared to healthy controls. Significant positive correlations were found between SOCS1 and IL-10, and between SOCS3 and IL-10. Significant inverse correlations were observed between SOCS1 and TNF-α, SOCS1 and RANKL, and SOCS3 and TNF-α. Increased SOCS-1, -2 and -3 mRNA levels in periapical granulomas may be related to the downregulation of inflammatory cytokines in these lesions; therefore, SOCS molecules may have a role in the dynamics of periapical granulomas development.